Evaluation of thermo-adaptability between Tharparkar (Bos indicus) and crossbred (Bos indicus X Bos taurus) calves in a controlled environment. (December 2022) - Jose, Bosco; Samad, Hari Abdul; Bharati, Jaya; Tejaswi, V.; Konda, Pranay; Sharun, Khan; Tripathi, Manoj K.; Kumar, Sai; Punetha, Meeti; Mohan, Divya; Verma, V.; Chouhan, Vikrant Singh; et al.
Abstract: The global warming driven climate change has increased the susceptibility of livestock around the globe to heat stress (HS), which reduces animal productivity and threatens the sustainability of marginal farmers. The objective of this investigation was to evaluate thermo-adaptability between Tharparkar calves (TC), an indigenous milch breed of India and crossbred calves (CC) during induced heat stress in controlled environment. For this purpose, 12 apparently healthy male calves (six in each group) aged 5–6 months, were selected. The experiment was conducted at physiologically comfortable temperature (25 °C), moderate HS (31 °C) and severe HS (37 °C) for 21 days each in a psychrometric chamber. In each experimental day, the calves were exposed to 6 h of heat. There were 7 days of acclimatization period before experiment and 10 days of recovery period at ambient temperature between each 21 day exposure period. During experimental period, the blood was collected at 1 st, 6 th, 11 th, 16 th, 21 st day and among ten-day recovery period the blood was collected at 5th day. Physiological responses, serum electrolytes, metabolic enzymes profiles, antioxidant capacity, oxidative stress status and general endocrine milieu were studied. Relative mRNA expression study of Heat Shock Protein (HSP) 70, HSP90, induced Nitric Oxide Synthase (iNOS) and endothelial NOS (eNOS) were carried out by qPCR. There was significant (p < 0.05) change in the displacement in rectal temperature, respiration rate, serum alanine aminotransferase level between two breeds at moderate and severe HS. Similar change was observed in total antioxidant capacity, superoxide dismutase, and endocrinological parameters. The comparatively lower mRNA expression of HSP70 and higher expression of HSP90 in TC than CC point the better thermo-adaptability of the same. The results of the experiment indicated that TC are more thermo-adaptable than CC at different modality of stress in controlled temperature conditions. Highlights: Decreased serum T3 level in Tharparkar calves indicates better adaptability to heat stress. Endothelial Nitric Oxide Synthase expression is higher in Tharparkar calves indicating superior heat dissipation efficiency. Lower expression of HSP70 and higher expression of HSP90 indicate better thermo-adaptability in Tharparkar calves. Tharparkar calves showed greater thermo-tolerance than crossbred cattle calves in a controlled climate.